EFEKTIVITAS PENAMBAHAN KULIT BUAH NAGA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis niloticus) - Apliana Dairu Kaka; Yudiana Jasmanindar; Priyo Santoso (Jurnal Aquatik, 2026)
Tilapia (Oreochromis niloticus) is a freshwater fishery commodity that has high economic value and is widely cultivated in Indonesia. The success of tilapia cultivation is greatly influenced by the quality of feed, so it is necessary to innovate effective, economical, and environmentally friendly feed ingredients. One potential alternative is the use of dragon fruit peel (Hylocereus sp.) which contains bioactive compounds such as antioxidants, polyphenols, and fiber. This study aims to determine the effectiveness of adding dragon fruit peel to feed on the growth and survival of tilapia. The results of the study are expected to provide information on the use of agricultural waste as a feed additive that can increase the productivity of tilapia cultivation sustainably. This study was conducted by raising tilapia in an aquarium using 4 treatments and 3 replications of feeding: 0% dragon fruit peel extract, 5% dragon fruit peel extract, 10% dragon fruit peel extract, 15% dragon fruit peel extract for 56 days, fish weight measurements were carried out every 7 days. The results of the ANOVA test showed that the addition of dragon fruit peel affected the growth of weight and length of tilapia. The weight growth of tilapia fed 15% dragon fruit peel extract reached 7.3 grams, and the absolute length growth reached 40 cm. The weight growth of tilapia fed 0% dragon fruit peel extract reached 6.7 grams and the absolute length reached 2.1 cm. The weight growth of tilapia fed 10% dragon fruit peel extract reached 2.9 grams and the absolute length reached 3.4 cm. The growth of tilapia fed 5% dragon fruit peel extract reached 2.7 grams and the absolute length reached 4.3 cm Keywords: Tilapia feed, dragon fruit peel, growth